Freedom of Press and Good Governance: an Indo-US Comparison (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Freedom of expression has always been emphasised as an essential basis  for the democratic functioning of a society. The right to know, receive and  impart information has been recognized within the right to freedom of  speech and expression. A citizen has a right to know about the activities  of the instrumentalities, the departments and the agencies of the State.  Press plays a crucial role in dissemination of information. A free and  vigilant Press is vital to restrain corruption and injustice by generat ing political discourse. Freedom of Press inevitably helps drive scientific  progress which in turn propels innovation and economic prosperity. Al though the expression “Freedom of Press” has not been used in Article  19 but it is implicit in the right of freedom of speech and expression. It is  the heart of social and political intercourse. Through this paper the authors try to emphasise the role of media on the  basis of Aristotle’s ‘theory of Politics’. Further, want to consider the US  position where there is an absolute Freedom of Press which has fostered  innovation and also comment upon the various tests laid down by the  Supreme Court of US to put reasonable restrictions upon such freedom.
Keywords: Press; Corruption; Freedom; Restrictions